Pembentukan Personal Branding (@nagotejena) Sebagai Psikolog Di Media Sosial Twitter - Cahyani, Ni Luh Putu Ika Putri; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2024)
Twitter is one medium that can be used to build broader personal branding. Nago Tejena and his account owner @nagotejena is a psychologist who actively writes educational tweets related to mental health issues. This research uses a qualitative approach with a descriptive research type to explain how the creation of Nago Tejena's personal branding as a psychologist on Twitter social media using Hubert K. Rampersad's Criteria for Effective Authentic Personal Branding concept. The results showed that Nago Tejena creates personal branding on Twitter social media as an educative psychologist by sharing insightful tweets with the audience, and Nago Tejena has a sense of concern for mental health issues so that she consistently shares educative tweets. This research also shows that Nago Tejena has complied with Hubert K. Rampersad's Criteria for Effective Authentic Personal Branding concept as the base for personal branding formation. Keeyword : Personal branding, Psychologist, Criteria for Effective Authentic Personal Branding, Twitter.